Development of object-oriented components for ATM Network Simulation with emphasis on Congestion Control / Sin Wai Kit - Sin, Wai Kit (2001)
Asynchronous Transfer Mode (ATM) is a very high-speed transmission technology. The barrage of technological advancements has continuously enhanced the network performance. There is an increasing dependence on the network. Thus, there is a need to accurately predict the impact of network and applications changes in the dynamic network environment. The network simulator is a tool to analyze the behavior of ATM networks without the expense of building a real network. The simulation of this simulator will give the results that imitate the real network environment. The aim of this project is to develop object-oriented components for an ATM Network Simulator that emphasis on congestion control mechanism. In this project, the ATM congestion control system makes use of leaky bucket and token bucket techniques. In addition, the object-oriented approach is used as the construction method for this simulator. The simulator consists of features like reusability, extensibility, portability as well as maintainability. Furthermore, the simulator is capable of multithreaded operations and platform independent. Thus, the developed simulator can run on different platforms like Windows or Unix.